Heat transfer and hysteresis characteristics in an elbow thermosyphon. (1st December 2021) - Hammouda, M.G.; Ewing, D.; Zaghlol, A.; Ching, C.Y.
Highlights: Experiments were performed in an elbow thermosyphon for incrementally increasing and decreasing power inputs. There was a significant hysteresis in the evaporator performance at moderate heat transfer rates (2 to 8 W/cm 2 ). There was a transition to a more dynamic flow regime at approximately 6 W/cm 2 . There was an improved performance in the upper or film region of the evaporator in the dynamic flow regimes. Abstract: Measurements were performed to characterize the performance of a grooved copper–water elbow thermosyphon with a fluid loading of 30%, typical of thermosyphons used for power electronic devices. The evaporator section was vertical, while the condenser section was inclined at an angle 8°to the horizontal. The performance of the device, characterized for incrementally increasing and decreasing heat transfer rates, shows a significant hysteresis in the evaporator performance at moderate heat transfer rates or fluxes (between 2 and 8 W/cm 2 ). The difference was due to changes in the upper portion or film region of the evaporator. Transients of the temperature suggest a change to a more dynamic flow regime in the evaporator at a heat flux of approximately 6 W/cm 2 . The transition occurred at similar heat fluxes for both the increasing and decreasing heat transfer rates. The improved performance in the upper or film region was observed after the dynamic regimes, suggesting it may be due to the wetting of the internal structure during this process. The effect was reduced with increasing operating temperature.